Morphological and molecular discordance in the taxonomic rearrangement of the Marmosops pinheiroi complex (Marsupialia: Didelphidae). Issue 7 (3rd October 2021) - Guimarães, Roger Rodrigues; Rocha, Rita Gomes; Loss, Ana Carolina; Mendes-Oliveira, Ana Cristina; Patterson, Bruce D.; Costa, Leonora Pires
Abstract : Marmosops is one of the most speciose genera of didelphid marsupials, is widely distributed in the Neotropical region, and has been the subject of several taxonomic and systematic revisions. Within the genus, the Pinheiroi complex is distributed in eastern Amazonia and recently has been split into three species, based only on morphology. We analysed both mitochondrial (CYTB) and nuclear (BRCA1) data of a large number of specimens of the Pinheiroi complex from the Tapajós region to test the three-species hypothesis. Our molecular data supported a conservative scenario of four lineages with high molecular divergence within the Pinheiroi complex: one from the Tapajós West bank (until now treated as M. marina ), another from the Tapajós East bank ( M. marina sensu stricto ), a third from the Xingú East bank ( M. woodalli ), and a fourth from the Amazon North bank ( M. pinheiroi ). But a scenario of five species within the Pinheiroi complex was not excluded. We restrict M. marina to the Tapajós-Xingú interfluve. Speciation in the Pinheiroi complex was estimated to have taken place in the late Miocene. Both Amazon and Tapajós Rivers have important roles in the differentiation of this complex, either by forming a complete barrier to an existing taxon or by restricting the gene flow between populations on each side of the river. The divergence of major clades on opposite sides of the Amazon and Tapajós Rivers occurred almost simultaneously during the Late Pliocene.